2022
DOI: 10.1136/svn-2022-001756
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutation contributing to clonal haematopoiesis is a risk factor of recurrent stroke in first-ever acute ischaemic stroke: a prospective cohort study

Abstract: BackgroundSomatic mutation contributes to clonal haematopoiesis of indeterminate potential (CHIP) is related to age and associated with a higher risk of stroke and atherosclerotic cardiovascular disease. Here, we investigated the prognostic significance of CHIP in a large first-ever acute ischaemic stroke (AIS) cohort and explored the underlying mechanisms.MethodsWe studied a prospective cohort of 6016 patients who had a first-ever AIS in China. Whole-genome sequencing was performed to identify CHIP. High-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
(45 reference statements)
1
9
0
Order By: Relevance
“…In our study, due to the WGS data being sequenced at a depth of 30X to broadly cover the whole genome, we have conservatively defined a variation as having a variant allele fraction (VAF) greater than 5% to enhance the robustness of our study. This threshold is higher than the 2%, or even 1.5%, typically referenced in previous study 4,7,11 . These measures were taken to ensure that our identification of DNMT3A ‐CHIP is both reliable and significant within the context of our research parameters.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In our study, due to the WGS data being sequenced at a depth of 30X to broadly cover the whole genome, we have conservatively defined a variation as having a variant allele fraction (VAF) greater than 5% to enhance the robustness of our study. This threshold is higher than the 2%, or even 1.5%, typically referenced in previous study 4,7,11 . These measures were taken to ensure that our identification of DNMT3A ‐CHIP is both reliable and significant within the context of our research parameters.…”
Section: Discussionmentioning
confidence: 90%
“…This threshold is higher than the 2%, or even 1.5%, typically referenced in previous study. 4 , 7 , 11 These measures were taken to ensure that our identification of DNMT3A ‐CHIP is both reliable and significant within the context of our research parameters. Furthermore, the clinical finding was verified in a mouse model in which inhibition of DNMT3A by RG108 increased infarct volume via proinflammatory pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, TET2 mutations are highly enriched in patients with ischemic stroke (57), suggesting a central role of TET2-driven CH in stroke pathogenesis (57). Other studies have identified DNMT3A (30.0%) and TET2 (11.4%) as the most common mutations in individuals with CHIP who experienced a first-ever acute ischemic stroke, and CHIP was specifically a s s o c i a t e d w i t h r e c u r r e n t s t r o k e i n p a t i e n t s w i t h hyperinflammation (56). TET2 showed the strongest association with total and ischemic strokes, while both DNMT3A and TET2 were associated with an increased risk of hemorrhagic stroke (55).…”
Section: Chip and Cardiovascular Risksmentioning
confidence: 99%